2023
DOI: 10.21931/rb/2023.08.01.81
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Fusarium oxysporum-caused watermelon wilt infection and testing of some hybrids' susceptibility to infection

Abstract: This study was conducted in the College of Agriculture, the University of Anbar, which aimed to diagnose the Fusarium oxysporium. The field survey results showed the spread of the disease in all areas for the seasons 2020-2021 and 2021-2022 in the governorates of Anbar, Baghdad, Salah al-Din, and Babylon. The infection rate ranged from 20-66%. The infection rate ranged from 20-66%, and the results of the phenotypic and molecular diagnosis showed the presence of the Fusarium oxysporium in the isolated samples. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The DNA extraction results for eleven isolated fungi from the roots and crowns of strawberry plants in different isolation areas revealed varying quantities of nucleic acid, ranging from 100 to 1500 base pairs (bp), as shown in Table 3. The partial diagnosis results using the PCR technique, based on the intergenic spacer region using primers (ITS1-ITS4), showed amplicons of (650) base pairs (bp) [13]. After migration on 2% agarose gel.…”
Section: Molecular Diagnosis Of Fungi Causing Root and Crown Rot Dise...mentioning
confidence: 99%
See 1 more Smart Citation
“…The DNA extraction results for eleven isolated fungi from the roots and crowns of strawberry plants in different isolation areas revealed varying quantities of nucleic acid, ranging from 100 to 1500 base pairs (bp), as shown in Table 3. The partial diagnosis results using the PCR technique, based on the intergenic spacer region using primers (ITS1-ITS4), showed amplicons of (650) base pairs (bp) [13]. After migration on 2% agarose gel.…”
Section: Molecular Diagnosis Of Fungi Causing Root and Crown Rot Dise...mentioning
confidence: 99%
“…symptoms include wilting, yellowing, and stunting of the aboveground parts. these pathogens destroy the root system, negatively impacting the aboveground growth [3]. scientific research has indicated that plant decline and mortality pose a significant challenge to strawberry production, despite the fact that crown and root diseases are among the key factors that determine production, particularly during the growing season.…”
Section: Introductionmentioning
confidence: 99%